PENINGKATAN MOTIVASI KERJA APARATUR DALAM PENYELENGGARAAN PEMERINTAHAN DI KANTOR KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Sakinah Sakinah (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
The purpose of the study was to find out about Increasing Apparatus Work Motivation in Government Administration at the Baranti District Office, Sidenreng Rappang Regency and to find out the factors that influenced the Increasing Apparatus Work Motivation in Government Administration at the Baranti District Office, Sidenreng Rappang Regency. The population of this study was 44 people, while the sample was 44 people. The data collection techniques used in this study were (1) observation, (2) interviews, (3) questionnaires, and (4) literature studies. The collected data was then analyzed using frequency and percentage tables. The results of this study indicate that the indicators of Increasing Apparatus Work Motivation in Government Administration at the Baranti District Office, Sidenreng Rappang Regency with an achievement of 67.57% in the good category. direct motivation consists of 66% praise factor, 68% award, 67% holiday allowance, 67% bonus with 67% achievement in good category, indirect motivation factor consists of a good machine or computer 69%, 66% bright workspace, 69% working atmosphere, 70% right placement, with 67.75 % achievement categorized as good.